The Influence of Career Development, Organizational Culture, and Employee Involvement on Employee Performance at the Nganjuk Regency Cooperative and Micro Business Office - Husniah, Alfiatul; Muchson, Mochamad (Universitas Nusantara PGRI Kediri, 2025)
Research aim: This study aims to examine whether Career Development, Organizational Culture, and Employee Involvement on Employee Performance at the Nganjuk Regency Cooperative and Micro Business Office Design/Method/Approach: This study uses a quantitative-based method. Sampling used a saturated sampling technique and obtained a sample of 44 respondents from the results of filling out a questionnaire to employees of the Nganjuk Regency Cooperatives and Micro Enterprises Office Analysis and processing of data using SPSS software Research Finding: This study shows the results of careerdevelopment, organizational culture and employee involvement have a partial and simultaneous significant effect on employee performance at the Nganjuk Regency Cooperatives and Micro Enterprises Office. Theoretical contribution/Originality: The researcher hopes that the results of this research can develop knowledge and a basis of thinking to help overcome the phenomena that occur in this research. Practitionel/Policy implication: In addition, it is a reading material in the development of science regarding employee performance and is the main reference for further research on related topics. Research limitation: the limitations of this study are the variables used that are less optimally representative and the object of research is limited to employees of the Nganjuk Regency Cooperatives and Micro Enterprises Office and limited data sources only come from questionnaires